Evaluating Quantum Dot Performance in Homogeneous FRET Immunoassays for Prostate Specific Antigen - Shashi Bhuckory; Olivier Lefebvre; Xue Qiu; Karl David Wegner; Niko Hildebrandt (Sensors, 2016)
The integration of semiconductor quantum dots (QDs) into homogeneous Förster resonance energy transfer (FRET) immunoassay kits for clinical diagnostics can provide significant advantages concerning multiplexing and sensitivity. Here we present a facile and functional QD-antibody conjugation method using three commercially available QDs with different photoluminescence (PL) maxima (605 nm, 655 nm, and 705 nm). The QD-antibody conjugates were successfully applied for FRET immunoassays against prostate specific antigen (PSA) in 50 µL serum samples using Lumi4-Tb (Tb) antibody conjugates as FRET donors and time-gated PL detection on a KRYPTOR clinical plate reader. Förster distance and Tb donor background PL were directly related to the analytical sensitivity for PSA, ...which resulted in the lowest limits of detection for Tb-QD705 (2 ng/mL), followed by Tb-QD655 (4 ng/mL), and Tb-QD605 (23 ng/mL). Duplexed PSA detection using the Tb-QD655 and Tb-QD705 FRET-pairs demonstrated the multiplexing ability of our immunoassays. Our results show that FRET based on QD acceptors is suitable for multiplexed and sensitive biomarker detection in clinical diagnostics.